PENGARUH PUTARAN DAN KECEPATAN TOOL TERHADAP SIFAT MEKANIK PADA PENGELASAN FRICTION STIR WELDING ALUMINIUM 5052 - Muhammad Iqbal; . Tarkono; Gusri Akhyar Ibrahim (Jurnal Ilmiah Teknik Mesin, 2014)
Aluminium is a metal that has a good resistance against corrosion, this is because the occurrence of the phenomenon of pasivasi. In addition to its resistance to corrosion, aluminium also has a lighter weight compared to steel, so aluminium is frequently used as one of the materials used in the manufacture of ships, especially on the upper deck of the building, insulation, fuel tanks and  freshwater tank.Welding is the process of connecting between two or more metal parts by using thermal energy.In general aluminum welding using fusion welding processes such as Metal Inert Gas and Metal Inert Gas, but on both of these methods there is possibility formation of defects are porosity, cracks and prone to occurringdeformationduringcooling processof dan the formation ofmetalwelding. The purpose of this study was to determine the effect of tool rotation and welding speed on the mechanical aspect of Aluminium 5052 with the friction stir welding method.The parameters of the   welding process is done on the research this is is the round tool and welding spee is is the round tool and welding speed.Round tool used there are two namely 1800 rpm and 1100 rpm. The speed of welding is also used there are two variations,namely 11.4 mm/min and 19.8 mm/min. As for the mechanical tests conducted there are three, namely testing the hardness, impact test, and tensile testing.The result of this research was the discovery that the round tool and welding speed greatly affect the mechanical properties of aluminium that has been welded. Because the tool is rotating faster increases the tensile strength of aluminium, while the small welding speed will increase the hardness of aluminum that has been welded. Keywords : aluminium, welding, friction stir welding, mechanical aspect of metals